IMPLEMENTASI FUNGSI STATISTIK KRIMINAL DALAM PENANGGULANGAN TINDAK PIDANA DI KOTA PADANG - Wiguna, Edryan (Universitas Ekasakti, 2020)
The compilation of criminal statistics must be used for decision making in dealing with crime. This research is a legal research with analytical descriptive specifications. The approach used is the Normative Juridical approach supported by empirical juridical. The urgency of compiling criminal statistics by the Padang Satreskrim Polres is to provide an overview / data about existing crime in the community, such as the number, frequency and distribution of the perpetrators and their crimes. The technique of compiling criminal statistics by Padang Police is to present the first data. The handling of criminal offenses by using criminal statistics is done by the Satreskrim Padang Police by applying two methods, namely a method to reduce repetition of crime and a method to prevent the first crime, which is a way aimed at preventing the occurrence of the first crime (the first crime) to be committed by someone and this method is also known as prevention (preventive) method.